Relocation preferences in the Era of Work From Home: Theoretical Framework - Kuźmar, Sławomir (Ekonomia i Prawo. Economics and Law, 2026)
Motivation: The COVID-19 pandemic catalysed an unprecedented global expansion of work-from-home (WFH) arrangements. While the prevalence of remote work has receded from its peak, it has stabilized since 2022 at levels well above those observed before the crisis. This shift indicates that WFH has evolved into a lasting feature of contemporary labour markets rather than a temporary disruption. Beyond transforming how work is organized, remote work influences daily routines, professional interactions, and social engagement. One domain where these effects are particularly salient is residential choice. By altering preferences regarding both housing attributes and location, WFH has the potential to reshape urban spatial patterns, reinforce suburbanization, and stimulate development in peripheral or rural areas. Aim: This paper aims to develop a multidisciplinary theoretical framework to examine how WFH shapes relocation processes. Building on neoclassical economics, relocation theories such as life-cycle and life-course approaches, and Stress-Threshold Model, it conceptualizes WFH as a distinct trigger of migration. The paper adopts a conceptual framework-building approach, synthesizing interdisciplinary theoretical perspectives through a systematic review of the literature. Results: The proposed framework emphasizes that WFH may significantly reshape stated residential preferences regarding both dwelling attributes and location, yet these shifts do not automatically translate into actual relocation. Whether preferences result in moves depends not only on individual dissatisfaction, as outlined in the Stress-Threshold Model, but also on market conditions and structural constraints. Relocation decisions therefore often reflect compromises rather than straightforward adjustments. The framework also suggests that short-distance mobility will remain central in hybrid work contexts, though broader spatial effects may emerge over time. These findings highlight avenues for future research, particularly qualitative studies on how preferences are negotiated across life-course stages and housing markets, and under what conditions WFH operates as a meaningful relocation trigger.